County-Level Social Capital and Bacterial Sexually Transmitted Infections in the United States. Issue 3 (March 2020) - Owusu-Edusei, Kwame; McClendon-Weary, Bryttany; Bull, Lara; Gift, Thomas L.; Aral, Sevgi O.
Abstract : Background: The association between county-level social capital indices (SCIs) and the 3 most commonly reported sexually transmitted infections (STIs) in the United States is lacking. In this study, we determined and examined the association between 2 recently developed county-level SCIs (ie, Penn State Social Capital Index [PSSCI] vs United States Congress Social Capital Index [USCSCI]) and the 3 most commonly reported bacterial STIs (chlamydia, gonorrhea, and syphilis) using spatial and nonspatial regression techniques. Methods: We assembled and analyzed multiyear (2012–2016) cross-sectional data on STIs and 2 SCIs (PSSCI vs USCSCI) on counties in all 48 contiguous states. We explored 2 nonspatial regression models (univariate and multiple generalized linear models) and 3 spatial regression models (spatial lag model, spatial error model, and the spatial autoregressive moving average model) for comparison. Results: Without exception, all the SCIs were negatively associated with all 3 STI morbidities. A 1-unit increase in the SCIs was associated with at least 9% ( P < 0.001) decrease in each STI. Our test of the magnitude of the estimated associations indicated that the USCSCI was at least 2 times higher than the estimates for the PSSCI for all STIs (highest P value = 0.01). Conclusions: Overall, our results highlight the potential benefits of applying/incorporating social capital concepts to STI control and prevention efforts. In addition, our results suggest that for the purpose of planning, designing, and implementing effective STI control and prevention interventions/programs, understanding the communities' associational life (as indicated by the factors/data used to develop the USCSCI) may be important. Abstract : Analyses of 2 county-level social capital indices (SCIs) indicated that they were negatively associated with sexually transmitted infection morbidity, although the association was higher for the United States Congress SCI compared with the Penn State SCI.Supplemental digital content is available in the text.